Are antioxidant enzymes essential markers in the diagnosis and monitoring of cancer patients – A review - Cecerska-Heryć, Elżbieta; Surowska, Oliwia; Heryć, Rafał; Serwin, Natalia; Napiontek-Balińska, Sylwia; Dołęgowska, Barbara (Clinical biochemistry, 2021)
•Non-small-cell lung cancer is usually characterized by decreased SOD and CAT activity and increased glutathione GST activity. Lowered SOD, CAT, and GPx activity is characteristic of bladder cancer. XOR, CAT, SOD and GPx expression is decreased in patients with ovarian cancer. Colorectal cancer is characterized by increased MnSOD expression (in vitro studies) and SOD expression while CAT, GPx, and GR are decreased (in vivo study).•SOD, CAT, and XOR are promising prognostic markers in cancer of the lung, bladder, ovarian, and colon. Reactive oxygen species (ROS) play a significant role in human cells. Excessive ROS production damages important macromolecules such as nucleic acids and can initiate and develop the carcinogenesis process. Antioxidant enzymes such as superoxide dismutase (SOD), catalase (CAT), glutathione reductase (GR), glutathione peroxidase (GPx), and xanthine oxidoreductase (XOR) are responsible for maintaining the balance between the functions of free radical formation and eliminating their excessive amounts. Based on the analyzed literature, the following conclusions can be made: 1. Antioxidant enzymes activity are important for diagnosing neoplastic diseases such as non-small-cell lung cancer, bladder cancer, ovarian cancer, and colon cancer. 2. Non-small-cell lung cancer is usually characterized by decreased SOD and CAT activity and increased glutathione GST activity. Lowered SOD, CAT, and GPx activity is characteristic of bladder cancer. XOR, CAT, SOD and GPx expression is decreased in patients with ovarian cancer. Colorectal cancer is characterized by increased MnSOD expression (in vitro studies) and SOD expression while CAT, GPx, and GR are decreased (in vivo study). 3. SOD, CAT, and XOR are promising prognostic markers in cancer of the lung, bladder, ovarian, and colon.